Life Cycle Nutrition : An Evidence Based Approach - Edelstein, Sari (US: J & B, 2015)
Revised and updated with the latest epidemiologic research, the Second Edition of Life Cycle Nutrition: An Evidence-Based Approach explores nutritional foundations and the growth, development and normal functioning of individuals through each stage of life. With subjects as diverse as media influences on eating, skipping breakfast, fruit juice consumption, and clinical nutrition, this text gives students current knowledge, helps them evaluate emerging knowledge, and prepares them to uncover new knowledge for the public, their clients, and themselves.Key Features: Evidence-Based Practice sections contains research articles that provide students with an opportunity to create peer-reviewed studies and clinical trials. Cultural Diversity Sidebars, integrated throughout the text, present issues that challenge students to think critically about the nutritional and health differences among ethnic groups. Interesting Vignettes, based on nutrition and health, enhance student understanding of the material presented.
Glossary 539-543p.; Index 545-559p.
Keywords: Adolescent nutrition; Adult evidence; Body mass index; Normal infant nutrition